Abstracts Accepted for Publication 2019
DOI: 10.1136/annrheumdis-2019-eular.6809
|View full text |Cite
|
Sign up to set email alerts
|

AB0372 EXPLORING REFRACTORY DISEASE & PERSISTENT SYMPTOMS IN RA/POLYJIA DESPITE BDMARDS: PATIENT & PROFESSIONAL EXPERIENCES

Abstract: BackgroundRefractory disease is defined as not achieving a low disease activity target despite DMARDs. This definition does not account for patients with well controlled inflammation who experience persistent symptoms, or who have a high perceived disease impact. Furthermore, variations in professionals understanding of refractory disease and related concepts exists, with potential discordance when compared to patients understanding.ObjectivesTo qualitatively explore patients and professionals understanding an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…A wider conceptual model was generated by the core research team to allow for consideration of the relationship between the domains and components excluded from the consensus definition and RIA, based on the Phase 1 development work [ 1 , 16 ]. The concepts and examples given here are based on findings from the systematic review highlighting the role of other contributing factors such as Serology and fixed disease factors such as disease duration [ 1 ] and qualitative work on patients’ and HCP’ experiences of RIA [ 16 ] (see S1 Fig ) such as social support and independence which included elements such as adjustment, resilience and illness/treatment beliefs which align with general theories of perceptions and adjustment to long-term illness. This followed a Biopsychosocial Formulation [ 19 , 20 ] (see Fig 3 ), with the Definition of RIA with Persistent Symptoms or Inflammation at the core, surrounded by Predisposing, Poor Prognostic, Perpetuating and Protective factors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A wider conceptual model was generated by the core research team to allow for consideration of the relationship between the domains and components excluded from the consensus definition and RIA, based on the Phase 1 development work [ 1 , 16 ]. The concepts and examples given here are based on findings from the systematic review highlighting the role of other contributing factors such as Serology and fixed disease factors such as disease duration [ 1 ] and qualitative work on patients’ and HCP’ experiences of RIA [ 16 ] (see S1 Fig ) such as social support and independence which included elements such as adjustment, resilience and illness/treatment beliefs which align with general theories of perceptions and adjustment to long-term illness. This followed a Biopsychosocial Formulation [ 19 , 20 ] (see Fig 3 ), with the Definition of RIA with Persistent Symptoms or Inflammation at the core, surrounded by Predisposing, Poor Prognostic, Perpetuating and Protective factors.…”
Section: Resultsmentioning
confidence: 99%
“…Components of RD were identified from: 1) qualitative interviews and focus groups with patients and HCPs [ 16 ], 2) systematic review of studies of RD in RA/PolyJIA [ 1 ], and 3) review and application of biopsychosocial theories regarding chronic illness and persistent symptoms. Firstly, an initial inductive thematic analysis of 25 patient (RA and Adult PolyJIA) and 32 HCP interviews conducted between August 2018 and April 2019 identified 17 components for common experiences of RD and persistent symptoms, whilst an additional seven were patient-specific (including JIA-specific) and four professional-specific [ 16 ] (see unpublished thematic map in S1 Fig ). This qualitative data analysis was part of a larger framework analysis, which involves five steps [ 17 , 18 ]: (i) familiarisation with data, (ii) preliminary thematic analysis to develop initial themes (presented here and [ 16 ]), with further steps occurring later which were: (iii) application of themes to the whole dataset systematically, (iv) reducing data from transcripts into summaries and organising these into a matrix (participants by themes), and (v) identifying patterns and relationships across participants and themes (manuscript in preparation).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wider conceptual model was generated by the core research team to allow for consideration of the relationship between the domains and components excluded from the consensus definition and RIA, based on the Phase 1 development work (4, 17). The concepts and examples given here are based on findings from the systematic review highlighting the role of other contributing factors such as Serology and fixed disease factors such as disease duration (4) and qualitative work on patients’ and HCP’ experiences of RIA (17) (see Suppl1) such as social support and independence which included elements such as adjustment, resilience and illness/treatment beliefs which align with general theories of perceptions and adjustment to long-term illness. This followed a Biopsychosocial Formulation (18, 19) (see Figure 3), with the Definition of RIA with Persistent Symptoms or Inflammation at the core, surrounded by Predisposing, Poor Prognostic, Perpetuating and Protective factors.…”
Section: Resultsmentioning
confidence: 99%
“…Components of RD were identified from: 1) qualitative interviews and focus groups with patients and HCPs (17), 2) systematic review of studies of RD in RA/PolyJIA (4), and 3) review and application of biopsychosocial theories regarding chronic illness and persistent symptoms. Firstly, inductive thematic analysis of 25 patient and 32 HCP interviews identified 17 components for common experiences of RD and persistent symptoms, whilst an additional seven were patient-specific (including JIA-specific) and four professional-specific (17) (see Suppl1). Secondly, a systematic review of existing definitions (4) identified three key elements of RD: 1) treatment, 2) presence or absence of inflammation and 3) symptoms and impact.…”
Section: Methodsmentioning
confidence: 99%